THE INFLUENCE OF ONLINE CUSTOMER REVIEWS AND PROMOTIONS ON PURCHASE DECISIONS OF GEN-Z USERS OF THE SHOPEE MARKETPLACE - Achmad Agil Agus; Gazali Amin; Dian Nirmasari (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to determine the influence of Online Customer Review and promotion on the purchase decision of active students of the Faculty of Economics and Business, Ichsan Sidrap University who use the Shopee marketplace. The focus of the research includes how customer reviews and promotions such as